BIODIVERSITY STUDY OF OLIVES IN NORTH OF SYRIA BY USING FRACTALS AND MOMENTS - Saher Al Bakeer (Mesopotamia Journal of Agriculture)
Syria has a huge diversity of Olives, and most of the references refer that Syria is one of the center of origin for olives therefore it is important to utilize these genetic resources in breeding programs of cultivated olive varieties, as first step to achieve this objective it is very important to identify these genetic resources by using new & easy methods for discrimination and identification the relatedness between the big number of verities and types . Therefore we tried to use an alternative method of morphological characterization based on study the seed characters in term of its length, surface grooves by using geometrical equations, this method could be considered more accurate than the morphological characterization by using the naked eye due to the fact that this method is based on the photos which is taken with high resolution camera and analyze these images using the computer software especially programmed for these studies is purposes which is guaranteed the high accuracy and impartiality in the results .The results shows that the studied wild types and the cultivated varieties were divided into two groups where the first group contains Sorani variety collected from Afrin, Salqin and Harem and samples from Maari local variety. The similarity percentage between Sorani variety cultivated in Salqin and Maari variety cultivated in Mardibsi is about 96% which is higher than similarity ratio between Sorani samples this is indicate that the two names referring for the same varieties. In addition this group contains some wild types from Rajo Like BR5 and BR3 . While the second group divided into two subgroups the first one contains samples of Zieti variety cultivated in Afren, Salqin and Harem and some wild types from Rajo and Wadi, while the second subgroup contains 3 wild types which are BW1, BW2 and BW5 from one site which is Wadi in Harem.